Битва желаний: [роман] / Д. Макнот - Макнот Джудит (АСТ:Хранитель, 2007)
Экземпляры: ЧЗ (20181122) / Инвентарный номер: 41453 / Цена: 55 / Сис.шифр: Р2 / Авт.знак: М 15 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)